A comparative analysis of the process of heating networks design in Poland and Norway on the example of Warsaw and Trondheim - Pachocki, Michał (Instal, 2021)
The article describes the process of designing heating networks in Poland and Norway. The similarities and differences between these processes are shown. Attention is drawn to the possibility of simplifying the design process in Poland, and thus accelerating the investment process.
Keywords: heating networks; design